凡德他尼治疗5例晚期复治肺腺癌患者的临床观察及相关文献回顾 (Zhongguo Fei Ai Za Zhi, 2012)
BACKGROUND AND OBJECTIVE: Vandetanib is a once-daily oral multi-target inhibitor of vascular endothelial growth factor receptor, epidermal growth factor receptor, and rearranged during transfection (RET) tyrosine kinases. The current study aimed to evaluate the effect and safety of vandetanib administered in refractory advanced lung adenocarcinoma patients. METHODS: Five patients who accepted chemotherapy and Tarceva therapy as first- and second-line treatments received vandetanib (300 mg, oral, once daily). RESULTS: The effects are stable disease on two patients (40%) and progressive disease on three patients (60%). With a median follow-up of 36 months, one patient remained on follow-up. The median progression free survival (PFS) is 2 months, and the mean overall survival is 22.6 months. The adverse events include rash (n=2), skin change (n=2), paronychia (n=2), asymptomatic QTc prolongation (n=2), ST-T change (n=1), diarrhea (n=1), and increased transaminase (n=1). CONCLUSION: There were lower incidences of severe side effects with vandetanib therapy in refractory advanced lung adenocarcinoma patients. The results of effect and safety of vandetanib are similar with the related reviewed articles.